Outcome of Conventional Trabeculectomy in Terms of Intraocular Pressure and Visual Acuity in Primary Open Angle Glaucoma: Doi:10.36351/pjo.v36i4.1086 - Shahid, Erum; Fasih, Uzma; Shaikh, Arshad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine the outcomes of conventional trabeculectomy in terms of decrease in Intra Ocular Pressure (IOP) and improvement in visual acuity in patients of primary open glaucoma, coming to a tertiary care hospital. Study Design: Retrospective case series. Place and Duration of Study: Ophthalmology department of a tertiary care hospital from January 2017 to December 2018. Methods: Patients undergoing trabeculectomy for Primary open angle glaucoma were included. Patients with repeated trabeculectomy, failed argon laser trabeculoplasty, advance cataract, corneal opacities and absolute glaucoma were excluded. All the trabeculectomies were done under retrobulbar anaesthesia after taking all aseptic measures. Primary outcome measures were preoperative and postoperative visual acuity, intraocular pressure, number of antiglaucoma medications and failed or successful trabeculectomy. Results: Total 52 patients underwent trabeculectomy. There were 36 (69.2%) males and 16 (30.8%) females. Mean age was 56.73 years ± 10.9 SD. Mean preoperative IOP was 30.96 ± 6.71 mm Hg, post operatively IOP at 1 year it was 15.6 ± 4.2 mm Hg. P value was <.000. Mean number of antiglaucoma medications was 3.03 and 1.19, pre and post-operatively respectively (p value <.000). Improvement in visual acuity after trabeculectomy was seen in 32 (61.5%) patients. Complete Surgical success was seen in 28 (53.8%) and qualified success in 21 (40.4%) patients. Failed trabeculectomy was seen in 3 (5.8%) patients. Conclusion: Conventional trabeculectomy is effective in lowering IOP in primary open angle glaucoma patients. It maintains IOP within normal range with and without anti-glaucoma medications at 1 year follow-up. Trabeculectomy significantly reduces number of anti-glaucoma medications. Key Words: Intraocular pressure, Primary open angle glaucoma, Trabeculectomy.